2015
DOI: 10.11646/zootaxa.3915.4.2
|View full text |Cite
|
Sign up to set email alerts
|

Redescription and taxonomic status of Paguristes praedator Glassell, 1937 and P. oxyophthalmus Holthuis, 1959 (Anomura: Paguroidea: Diogenidae), with an emendation to the diagnosis of the genus Areopaguristes Rahayu & McLaughlin, 2010

Abstract: The taxonomic status of Paguristes praedator Glassell, 1937, and Paguristes oxyophthalmus Holthuis, 1959, is reevaluated, and the two species redescribed and illustrated in detail. Both species are transferred to the genus Areopaguristes Rahayu & McLaughlin, 2010, a genus previously defined to accommodate species of Paguristes sensu lato with 12 pairs of gills instead of 13. Two important characters in both species were found to differ or have not been mentioned in the current definition of Areopaguristes,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…List of Paguroidea known from the Brazilian coast. [1, species present in Brazil collections reported herein; 2, previously reported as Paguristes oxyophthalmus, see Ayón-Parente et al (2015); 3, previously confused in Brazil under C. vittatus (Bosc, 1802), see Negri et al( 2014); 4, mentioned in Coelho et al (2007) as Petrochirus insignis under Dardanus venosus, 5, previously reported as Paguristes calliopsis, see Rahayu (2005)]. …”
Section: Introductionmentioning
confidence: 86%
“…List of Paguroidea known from the Brazilian coast. [1, species present in Brazil collections reported herein; 2, previously reported as Paguristes oxyophthalmus, see Ayón-Parente et al (2015); 3, previously confused in Brazil under C. vittatus (Bosc, 1802), see Negri et al( 2014); 4, mentioned in Coelho et al (2007) as Petrochirus insignis under Dardanus venosus, 5, previously reported as Paguristes calliopsis, see Rahayu (2005)]. …”
Section: Introductionmentioning
confidence: 86%